Collective health through the centuries; the construction of health knowledge in the face of different diseases that plagued humanity (Research, Society and Development, 2020)
Objective: In view of the necessary and constant search for the contingent and for the radicality and rationality of the historical argument in the analyzes of the field of Public Health, this study aimed to carry out a narrative review, contextualizing some changes that occurred in the understanding of collective health in the face of various outbreaks of public health throughout history. For this, a literature search was carried out with consultation to the SCIELO, MEDLINE databases, portals of the Ministry of Health, Pan American Organization and World Health Organization. Based on the PICO strategy (Patient or problem, Intervention, Control or Comparasion, Outcomes) and based on the question '' With regard to security, what measures have been taken in the different public health crises to control the spread of disease according to the social context? Methods: The methodology used was the bibliographic, combined with a contextualization of the data, the results of which varied considerably between decades, where studies were carried out under conceptual, empirical and terminological views, and it means doing science within the scope of qualitative methods and techniques. Conclusion: Through the research carried out in the present study, it was possible to discuss the evolution of knowledge in health in an enriching way and verify that, over the centuries, public health practices have become increasingly effective and disseminated.